Calibrating Fake Feature Statistical Distribution for Few-Shot Object Detection - Liu, Lanlan; Sima, Haifeng (International Journal of Computer Science and Information Technology, 2025)
The booming development of object detection has benefited from rich datasets. However, obtaining a large amount of labeled data for scarce objects is expensive. Few-Shot Object Detection (FSOD) has garnered significant attention, aiming to learn new categories with only a small number of labeled samples. In this paper, we propose a novel FSOD model based on data augmentation, namely Calibrating Fake Feature Statistical Distribution for Few-Shot Object Detection (CFSD). First, we utilize feature-specific generative adversarial methods to synthesize fake features, addressing the issue of overfitting in the detection head and classifier when dealing with limited samples. However, due to the model’s insufficient training samples, the distribution of the generated fake features in the feature space tends to lean towards the base category. To tackle this issue, we design a distribution calibration module to adjust the statistical distribution of fake features, aligning it with that of novel category features. Finally, we conducted tests on the Pascal VOC and MS COCO datasets, and the results unequivocally confirmed the effectiveness of our method. The test results outperform existing FSOD-based methods and other data augmentation-based methods.